2014
DOI: 10.1037/a0036377
|View full text |Cite
|
Sign up to set email alerts
|

Syntactic priming during sentence comprehension: Evidence for the lexical boost.

Abstract: Syntactic priming occurs when structural information from one sentence influences processing of a subsequently encountered sentence (Bock, 1986; Ledoux et al., 2007). This article reports two eye-tracking experiments investigating the effects of a prime sentence on the processing of a target sentence that shared aspects of syntactic form. The experiments were designed to determine the degree to which lexical overlap between prime and target sentences produced larger effects, comparable to the widely observed ‘… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
51
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 63 publications
(193 reference statements)
5
51
1
2
Order By: Relevance
“…Because the type of target sentence was not predictable based on the type of prime sentence that appeared on a given trial, participants should not have been able to develop a strategy that relied on them predicting the imminent arrival of a particular kind of target sentence. As noted above, previous studies have demonstrated that semantic repetition, by itself, does not lead to facilitated processing of syntactically challenging parts of target sentences (Carminati et al, 2008; Tooley et al, 2009; Traxler & Tooley, 2008; Traxler et al, in press). The current experiments provide a further test of the semantic facilitation hypothesis.…”
Section: Syntactic Priming In Comprehensionmentioning
confidence: 80%
See 4 more Smart Citations
“…Because the type of target sentence was not predictable based on the type of prime sentence that appeared on a given trial, participants should not have been able to develop a strategy that relied on them predicting the imminent arrival of a particular kind of target sentence. As noted above, previous studies have demonstrated that semantic repetition, by itself, does not lead to facilitated processing of syntactically challenging parts of target sentences (Carminati et al, 2008; Tooley et al, 2009; Traxler & Tooley, 2008; Traxler et al, in press). The current experiments provide a further test of the semantic facilitation hypothesis.…”
Section: Syntactic Priming In Comprehensionmentioning
confidence: 80%
“…These studies indicate that semantic repetition, by itself, is not sufficient for facilitated processing of syntactically challenging portions of sentences (Tooley et al, 2009). iii They indicate also that participant strategies are likewise not sufficient to facilitate processing of syntactically challenging portions of sentences (Traxler & Tooley, 2008; Traxler et al, in press). …”
Section: Syntactic Priming In Comprehensionmentioning
confidence: 99%
See 3 more Smart Citations